Find the function h(x) = f(x) - g(x) if f(x) = 3x and g(x) = 32x - 3x.

Question

Asked 11/18/2014 11:10:03 AM

Updated 12/27/2014 8:58:09 AM

2 Answers/Comments

Flagged by yeswey [12/27/2014 8:56:41 AM]

s

Question

Asked 11/18/2014 11:10:03 AM

Updated 12/27/2014 8:58:09 AM

2 Answers/Comments

Flagged by yeswey [12/27/2014 8:56:41 AM]

Rating

8

if f(x) = 3x and g(x) = 32x - 3x,

h(x) = f(x) - g(x) = 3x - (32x - 3x) = 3x - 32x + 3x = -26x

h(x) = f(x) - g(x) = 3x - (32x - 3x) = 3x - 32x + 3x = -26x

Added 12/27/2014 8:58:09 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [12/27/2014 9:02:53 AM]

In the equation 3x 2 + 6x = 12, the value of c is: **Weegy:** 3x + 4 = 6x + 1; 4 - 1 = 6x - 3x; 3 = 3x; x = 3/3; x = 1 (More)

Question

Updated 11/11/2014 7:29:05 PM

1 Answer/Comment

34,468,971

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 842 [Total 6715] Ratings 19 Comments 652 Invitations 0 Offline

There are no comments.